Optimum design calculation of eggs incubator: Case study - Al-Zaidi, Ali (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
This study was achieved to find an optimum design for eggs incubator where the resources of this field is very limited. The most important factors were putted forward including the dimensions of each element. The energy required in operation periods was calculated. Where the operation time consists of two periods (the first period takes 17 days and the second period from the 18th day to the 21 day). The results shown an excellent efficiency, however, some eggs were failed due to some physiology justifications. Some of eggs were taken longer time to hatch due to long storage time or the eggs were in a bigger size.